Prevalence and risk factors of mild cognitive impairment and dementia in northern Peru - Zegarra-Valdivia, Jonathan; Pérez-Fernández, Leandro; Casimiro-Arana, Milagros; Arana-Nombera, Harold; Gallegos-Manayay, Viviana Nayelli; del Rosario Oliva-Piscoya, María; Alamo-Medina, Reyna; Abanto-Saldaña, Eduardo; Vásquez-Zuñe, Nobuko; Pérez, Lisseth Detquizan; Gutierrez-Flores, Diana; Tantarico, Leslie Lozada; et al. (Frontiers in Public Health, 2025)
BackgroundGlobal dementia prevalence estimates indicate a growing burden, particularly in Low- and Middle-Income Countries (LMICs). Factors such as education, socioeconomic status, and limited public health interventions contribute to the development of Alzheimer’s disease and other dementias. This study aimed to determine the prevalence of Mild Cognitive Impairment (MCI) and dementia in middle-aged and older adults from northern Peru, as well as identify possible associated risk factors.MethodsA cross-sectional study was conducted with 385 participants aged 40 to 85 years from Chiclayo, Peru. Cognitive impairment was assessed using the Rowland Universal Dementia Assessment Scale (RUDAS) and INECO Frontal Screening (IFS). Functional activity and depression were evaluated with the Pfeffer Functional Activities Questionnaire (PFAQ) and Patient Health Questionnaire-9 (PHQ-9). Participants were classified as controls, MCI, or dementia based on education-adjusted cutoff scores of those scales through cognitive system classification tools.ResultsAccording to the results, 31.4% of the sample consisted of subjects without cognitive impairment, 40.5% were identified as possible cases of MCI, and 24.9% as possible cases of dementia. However, the percentages by age group are high. A lower educational level is associated with older age and correlates with lower cognitive scores and functional impairment. Age, hypertension, and hearing loss were significant risk factors for MCI and dementia.ConclusionThe prevalence of possible MCI and dementia in a city in north Peru is high, with a predominance of MCI and dementia in older adults. Age, low education, hypertension, and hearing loss are potential risk factors for cognitive impairment.